1980
DOI: 10.3758/bf03326486
|View full text |Cite
|
Sign up to set email alerts
|

Heart-rate reactivity to reminder treatment predicts test performance in rats given ECS following training

Abstract: Two experiments compared the capacity of reminder treatments to modify retention performance in rats either strongly trained and given ECS or weakly trained and given no ECS. Heart rate was monitored during the reminder sessions. In Experiment 1, the factorial combinations of stimulation of the mesencephalic reticular formation (MRF) (present, absent) followed by the presentation of the cue originally paired with foots hock in training, a tone (present, absent), were evaluated as reminder stimuli. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Given the absence of a significant interaction between prior exposure treatment and baseline heart rate activity, the raw data were transformed to suppression ratios (DeVietti & Porter, 1969;Wittman & DeVietti, 1981) for subsequent analyses. This transfonnation compares heart rate activity during CS presentation with heart rate activity occurring prior to stimulus introduction (baseline measure).…”
Section: Resultsmentioning
confidence: 99%
“…Given the absence of a significant interaction between prior exposure treatment and baseline heart rate activity, the raw data were transformed to suppression ratios (DeVietti & Porter, 1969;Wittman & DeVietti, 1981) for subsequent analyses. This transfonnation compares heart rate activity during CS presentation with heart rate activity occurring prior to stimulus introduction (baseline measure).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are numerous examples of memory recovery following post-training amnesic treatments and the range of conditions is similar to the cue-dependent amnesia domain (see Table 1). Since the 1960s, research has shown that after post-training amnesia, the original conditioned response can spontaneously recover over time (e.g., Cooper & Koppenaal, 1964; also see, Parsons & Davis, 2011;Quartermain, McEwen, & Azmitia, 1970Squire & Barondes, 1972;Zinkin & Miller, 1967) or when the original US (i.e., reinstatement; e.g., Misanin, Miller, & Lewis, 1968; also see, Devietti & Hopfer, 1974;Land, Bunsey, & Riccio, 2000;Miller, Ott, Berk, & Springer, 1974;Miller & Springer, 1972;Quartermain, McEwen, & Azmitia, 1970;Radyushkin & Anokhin, 1999) or CS are presented again before testing (Dekeyne, Deweer, & Sara, 1987;Deweer, Sara, & Hars, 1980;Deweer & Sara, 1981;Gordon & Mowrer, 1980;Wittman & DeVietti, 1980). Further support for that view comes from studies demonstrating that recovery from post-training amnesia can be induced by the amnesic treatment itself (i.e., state-dependency learning; Hinderliter, Webster, & Riccio, 1975;Mactutus, McCutcheon, & Riccio, 1980;Mactutus & Riccio, 1978;Overton, 1964Overton, , 1972Thompson & Neely, 1970;Vardaris, Gaebelein, & Riccio, 1973), including protein synthesis inhibitors (e.g., Bradley & Galal, 1988).…”
mentioning
confidence: 99%